2020
DOI: 10.1007/s11356-020-10571-z
|View full text |Cite
|
Sign up to set email alerts
|

Energy conservation and carbon reduction potential for solid waste in China

Abstract: The generation of solid waste has increased dramatically in China, owing largely to the rapid development and expansion of the Chinese economy. The management of solid waste is critical and becoming a challenge for some cities in China. Waste recycling is an effective solution to solid waste management and seeks to balance ecological sustainability with economic improvements. This study assessed the energy conservation and CO 2 emission reduction potential of solid waste using an embodied energy/ carbon model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The study found that most of the carbon emissions from steel come from the product stage. The use of recycled steel emits half the amount of carbon dioxide of virgin steel [57]. Moreover, it has a higher recycling rate and more mature recycling technology [58].…”
Section: Carbon Reduction Potential Of Recycling Cdrwmentioning
confidence: 99%
“…The study found that most of the carbon emissions from steel come from the product stage. The use of recycled steel emits half the amount of carbon dioxide of virgin steel [57]. Moreover, it has a higher recycling rate and more mature recycling technology [58].…”
Section: Carbon Reduction Potential Of Recycling Cdrwmentioning
confidence: 99%
“…The mechanism of the driving forces influencing RWH generation tends to be regionally different. Managing the massive RWH has inevitably become a tough challenge for the Chinese government [32,33]. It is suggested that local governments need to make appropriate plans according to local conditions and economic and social development to determine the mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The generation of solid waste has increased dramatically in the world, owing largely to the rapid development and expansion of the economy. The management of solid waste is critical and becoming a challenge for some countries in the world (Wang M. X. et al 2020) (Obiora et al 2021). Based on the case study of solid waste, this study aims to: 1) examine the defects of the three typical methods used for distinguishing the SBs; 2) discover the candidate PRs and 3) explore the potential mechanism between the SBs and PRs.…”
Section: Introductionmentioning
confidence: 99%